ENVIRONMENTAL AND RADIOLOGICAL POLLUTION IN CREEK SEDIMENT AND WATER FROM DUHOK, IRAQ - S. Abdullah, K. M.; Ahmed, M. T. (The Nucleus, 2012)
The activity concentrations of terrestrial ( 226Ra, 232Th and 40K) and anthropogenic gamma emitting radionuclides (137Cs) have been measured in 28 creek water and sediment samples randomly selected in different locations of Duhok governorate. The governorate is located in the northwest Kurdistan region of Iraq. Determination of the human health risk from the three exposure pathways (External radiation, Inhalation and Ingestion) was carried out. In addition, the chemical analysis was performed for the 13 surface water samples for reliability of physical results. Gamma spectroscopy system with a shielded well type NaI(TI) detector used for 40000 sec per sample. The data analysis included elemental concentrations, air absorbed dose rate, annual effective dose rate and external hazard index (radium equivalent activity). The average of 49.81±1.69 nGyh-1 in sediment and 21.19±1.32 nGyh-1 in water samples were below the world average value of 57nGyh-1. The corresponding annual effective dose rates outdoor estimated for sediment and surface water were 61.13±2.1µSvy-1 and 26.01±1.62 µSvy-1 respectively. The calculated external hazard indexes (Hex) 0.29+0.01 for sediment and 0.112+0.007 surface water samples. These values showed that all samples were well below the hazard limit of unity. The RESRAD-6.5 computer code was used to analyze the dose per unit release of a specified radionuclide and the health risk from the three exposure pathways. RESRAD code showed over estimation of the results of annual effective dose rates, even though the results were within the background level. The average value of activity concentrations of the radionuclides of sediment samples by the code was 0.108 mSvy-1 compared to our calculations. The probability of human cancer risk lifetime of a hypothetical contamination consisted of the highest value of the activity concentrations of terrestrial radionuclides and 137Cs is 17 people from 10000. The chemical analysis of the surface water samples showed compatibility with radiological results in terms of the solubility of isotopes. The radiological impact due to exposure pathways, as analyzed by RESRAD software and from other results indicated that the environment of the governorate was clean and suitable for living.